To the problem of influence of the third invariant of stress deviator on the process of longterm deformation of nonlinear viscoelastic materials - Romanov, A. V.; Fernati, P. V. (Київський національний університет імені Тараса Шевченка, 2019)
The problem on the influence of stressed state on the process of long-term deformation of nonlinear viscoelastic materials under the simple and quasi-simple modes of loading by introduction of the function with the parameter of Lode angle into the defining equations is considered. The mentioned function is determined by analysis of base experimental data obtained from the base experiments on axial tension and pure torsion. Physical and mechanical properties of nonlinear viscoelastic solids are defined by the correspondence between the invariants of deformation tensors and tensions according to the modified nonlinear Rabotnov’s model for viscoelasticity. The heredity kernels are given by the fractional-exponential function. The constructed defining equations are verified experimentally for the problems of determination of nonlinear creep deformations under combined loading applied to the thin-walled tubular elements made of polyethylene of high density and low pressure polyethylene. As a result of juxtaposition of experimental data and calculations it is a stated that allowing for the type of stressed state improves their agreement qualitatively and quantitatively.Key words: nonlinear viscoelastic materials, tension with torsion, creep strains, Lode angle.Pages of the article in the issue: 186-189Language of the article: Ukrainian